Effectiveness of Government Policy in Home Ownership Credit Offer Program with Zero Percent Down Payment during the Covid-19 Pandemic - Mayanti, Yuni (Journal of Economicate Studies, 2021)
This article discusses the effectiveness of government policies in home ownership credit offering program with zero percent down payment during the covid-19 pandemic. The writing of this article uses a qualitative method through a literature study approach. Data sources are taken from trusted sources and books as references. The data analysis technique was carried out by means of the researcher’s interpretation of the data obtained. The results of the discussion showed that in the face of the COVID-19 pandemic, the government issued a monetary policy to restore the national economy and boost the economy in Indonesia which was sluggish due to the COVID-19 pandemic. Monetary policy carried out by the government that is Bank Indonesia issued a home ownership credit offering program with zero percent down payment effective from March 1, 2021 to December 31, 2021. The home ownership credit offering program with zero percent down payment received a positive response from the public, developers and banks and based on data from Central Bureau of Statistics Republic of Indonesia that zero percent down payment program during the covid-19 pandemic grew zero point ninety four percent during the first 3 months of 2021 so that the government’s policy in offering home ownership credit programs with zero percent down payment was effective in encouraging the economy in Indonesia, especially in the property sector in the context of recovery national economy. While in Islamic financial institutions, monetary policy is viewed from the financing of home ownership with a murabahah contract.